2017
DOI: 10.3390/ijerph14111320
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mental Health Disorders and Reports to Child Protective Services: A Birth Cohort Study

Abstract: Background. Existing literature has documented a strong relationship between parental mental illness and child maltreatment, but little is known about the prevalence of mental illness among childbearing women. In the present study, linked administrative records were used to identify the prevalence of maternal mental health (MH) disorders documented at birth and determine the associated likelihood of maltreatment reports during infancy. Materials and Methods. Vital records for California’s 2006 birth cohort wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…Although it is hard to distinguish the role that this involvement played in subsequent substance use or suicidal ideation, there has been documentation of greater Child Protective Services involvement among mothers with mental health diagnoses, with amplified effects among those with mental health and SUD disorders, compared to mothers without such diagnoses. 36 Our finding highlights a potential missed opportunity for coordination between child welfare and obstetric or mental health providers to offer support and resources. 37 Programs such as Healthy Start; Special Supplemental Nutrition Program for Women, Infants, and Children; and organizations focused on home visitation and intimate partner violence prevention may also regularly interact with pregnant and postpartum people and could consider ways to offer screening and linkage to needed care and resources.…”
Section: Exhibitmentioning
confidence: 77%
“…Although it is hard to distinguish the role that this involvement played in subsequent substance use or suicidal ideation, there has been documentation of greater Child Protective Services involvement among mothers with mental health diagnoses, with amplified effects among those with mental health and SUD disorders, compared to mothers without such diagnoses. 36 Our finding highlights a potential missed opportunity for coordination between child welfare and obstetric or mental health providers to offer support and resources. 37 Programs such as Healthy Start; Special Supplemental Nutrition Program for Women, Infants, and Children; and organizations focused on home visitation and intimate partner violence prevention may also regularly interact with pregnant and postpartum people and could consider ways to offer screening and linkage to needed care and resources.…”
Section: Exhibitmentioning
confidence: 77%
“… 32 , 33 , 34 , 35 This decision is consistent with other recent studies using CPS records. 16 , 36 , 37 , 38 , 39 The screened-in referrals were stratified by maltreatment type (physical abuse or neglect) and included cases screened-in for an alternative response. Cases with concern for both physical abuse and neglect were included in both groups.…”
Section: Methodsmentioning
confidence: 99%
“…For example, parents who have an anxiety disorder are less likely to grant their children autonomy and more likely to demonstrate lower levels of sensitivity (18), while children of parents with psychosis might be directly involved in a parent's delusions (19). After controlling for other risk factors at birth, Hammond et al (20) found that two thirds of infants of mothers with a psychotic disorder were reported to child protection services. This was four times that of infants of mothers without a mental illness.…”
Section: Introductionmentioning
confidence: 99%